2020
DOI: 10.3390/microorganisms8101550
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal and Nutrient Supplement Responses in Rumen Microbiota Structure and Metabolites of Tropical Rangeland Cattle

Abstract: This study aimed to characterize the rumen microbiota structure of cattle grazing in tropical rangelands throughout seasons and their responses in rumen ecology and productivity to a N-based supplement during the dry season. Twenty pregnant heifers grazing during the dry season of northern Australia were allocated to either N-supplemented or un-supplemented diets and monitored through the seasons. Rumen fluid, blood, and feces were analyzed before supplementation (mid-dry season), after two months supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Both breed and season can affect the growth, rumen fermentation, methane emissions, feed utilization, and other animal productivity traits of ruminants in an age-dependent manner [ 25 , 26 , 30 , 31 , 32 ]. Many studies have compared and evaluated the difference between breeds and seasons [ 27 , 36 , 53 ]. The present study compared and examined how breed and season might affect the growth performance, rumen fermentation characteristics, methane emissions, and the rumen microbiota using both Holstein and Jersey steers as animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both breed and season can affect the growth, rumen fermentation, methane emissions, feed utilization, and other animal productivity traits of ruminants in an age-dependent manner [ 25 , 26 , 30 , 31 , 32 ]. Many studies have compared and evaluated the difference between breeds and seasons [ 27 , 36 , 53 ]. The present study compared and examined how breed and season might affect the growth performance, rumen fermentation characteristics, methane emissions, and the rumen microbiota using both Holstein and Jersey steers as animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal shifting of the rumen microbiota has been reported in grazing dairy cows by Noel et al [ 36 ], but the changes in pastures confounded any potential seasonal effect. Martinez-Fernandez et al [ 53 ] also observed that the bacterial community of grazing cattle had changed at mid-dry and wet season with or without a Nitrogen-based supplement. However, the differences in nutrient contents of grazing pastures at different seasons does not represent the seasonal influence of feedlot cattle with same TMR.…”
Section: Discussionmentioning
confidence: 99%
“…In Wagyu crossbred steers, Connolly et al [4] found that blood metabolites were either positively or negatively correlated with key production traits including growth rate, carcass weight, and subcutaneous and intramuscular fat, thus potentially offering biomarkers that could be used for individual steer selection for feedlot performance. Whereas published reports on the impacts of seasonal and dietary nutrient supplementation on rumen microbiota structure and metabolites of beef cattle abound [5][6][7], to our current knowledge of the published literature, there are no existing peer reviewed reports on the plasma metabolite profiles of tropical northern Australian beef cattle steers supplemented with the tropical legume Desmanthus. Our present research was intended to fill this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…The Northern Australian beef industry is defined by an extensive grazing system in dry tropical rangelands. In this particularly low N environment, undernutrition is the major issue, especially during the dry winter season [5]. Animals that efficiently convert feed into meat or body mass have a high difference between their actual feed intake and the expected feed requirements for maintenance and growth (low residual feed intake, RFI) over a particular time period [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation